France and the German question, 1945-1990 - Bozo, Frédéric; Wenkel, Christian (Berghahn, 2019)
"In the immediate aftermath of World War Two, the victors were unable to agree on Germany's fate, and the separation of the country--the result of the nascent Cold War--emerged as a de facto, if provisional, settlement. Yet East and West Germany would exist apart for half a century, making the 'German question' a central foreign policy issue--and given the war-torn history between the two countries, this was felt no more keenly than in France. Drawing on the most recent historiography and previously untapped archival sources, this volume shows how France's approach to the German question was, for the duration of the Cold War, both more constructive and consequential than has been previously acknowledged"--